2015
DOI: 10.1111/asj.12416
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and relationships of 16 Asian and European cattle populations using DigiTag2 assay

Abstract: In this study, we genotyped 117 autosomal single nucleotide polymorphisms using a DigiTag2 assay to assess the genetic diversity, structure and relationships of 16 Eurasian cattle populations, including nine cattle breeds and seven native cattle. Phylogenetic and principal component analyses showed that Bos taurus and Bos indicus populations were clearly distinguished, whereas Japanese Shorthorn and Japanese Polled clustered with European populations. Furthermore, STRUCTURE analysis demonstrated the distinct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
4
18
0
Order By: Relevance
“…We obtained blood samples from Japanese Black cattle ( n = 542), Japanese Shorthorn cattle ( n = 109), Japanese Brown cattle ( n = 106), Angus cattle ( n = 118), and Holstein cattle ( n = 204) raised at Tokachi, Ohu, Iwate, Tottori, Miyazaki, and Kumamoto stations of NLBC, respectively, in order to screen for the two non-synonymous SNPs. Japanese Black cattle, Japanese Shorthorn cattle, and Japanese Brown cattle are beef cattle called “Wagyu” [ 44 ], with different genetic background [ 45 ]. For Japanese Black cattle and Holstein cattle, the samples were selected using the criteria of at most 5 progenies in each sire, and these animals were low relatives with the progeny of 164 sires and 110 sires, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained blood samples from Japanese Black cattle ( n = 542), Japanese Shorthorn cattle ( n = 109), Japanese Brown cattle ( n = 106), Angus cattle ( n = 118), and Holstein cattle ( n = 204) raised at Tokachi, Ohu, Iwate, Tottori, Miyazaki, and Kumamoto stations of NLBC, respectively, in order to screen for the two non-synonymous SNPs. Japanese Black cattle, Japanese Shorthorn cattle, and Japanese Brown cattle are beef cattle called “Wagyu” [ 44 ], with different genetic background [ 45 ]. For Japanese Black cattle and Holstein cattle, the samples were selected using the criteria of at most 5 progenies in each sire, and these animals were low relatives with the progeny of 164 sires and 110 sires, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we strongly suspected that these BLV-infected JB cattle might have significantly increased number of lymphocytes but was hardly detected. Because JB and Holstein (Hol) cattle are genetically distinct species, the disease susceptibility or hematological characteristics after BLV infection might differ [ 17 , 22 ]. The purpose of this study was to evaluate the expansion of lymphocytes in BLV-infected JB cattle and to modify the EC Key for JB cattle.…”
mentioning
confidence: 99%
“…However distribution of these polymorphisms in the zebu cattle remains unclear. Since remarkable differences in allelic frequencies of various genes between taurine and zebu cattle populations have been reported Kaneda et al 2011;Yonesaka et al 2016, Okuda et al 2017), whether or not these polymorphisms observed in populations of taurine cattle are also observed in populations of zebu cattle is of particular interest. In the present study, we found that the polymorphisms of EDG1, NCAPG, and MC1R genes reported in taurine cattle were also observed in the population of Pesisir cattle.…”
Section: Resultsmentioning
confidence: 99%